Van Nostrand's Encyclopedia of Chemistry 2005
DOI: 10.1002/0471740039.vec1609
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Coatings

Abstract: Liquid‐Phase Metallizing Techniques Gas‐Phase Metallizing Techniques Vacuum‐Phase Metallizing Techniques Metallizing by Direct Physical or Thermal Bonding Environmental Concerns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Krulik and Mandich [25] reported that the Au(I) thiosulphatesulphite mixed ligand system functions as an autocatalytic bath in the absence of any conventional reducing agent. They believed that the thiosulphate-sulphite mixture itself is a reducing agent system, and that sulphite functions as the main reducing agent in this bath.…”
Section: Introductionmentioning
confidence: 99%
“…Krulik and Mandich [25] reported that the Au(I) thiosulphatesulphite mixed ligand system functions as an autocatalytic bath in the absence of any conventional reducing agent. They believed that the thiosulphate-sulphite mixture itself is a reducing agent system, and that sulphite functions as the main reducing agent in this bath.…”
Section: Introductionmentioning
confidence: 99%
“…The baths using hydrazine (22,23) and sodium hypophosphite (24) as the reducing agent were developed. More recently, it was reported that the deposition of gold in the thiosulfatesulfite mixed ligand system takes place autocatalytically even without adding any reducing agent (25). The present authors and collaborators have since conducted a detailed study on this aspect, which led to the conclusion that the bath without any added reducing agent functions as a substrate-catalyzed system rather than an autocatalytic system.…”
mentioning
confidence: 67%
“…The thiourea bath was developed and subsequently improved by a group of investigators at Hitachi, Ltd. (17,25). Basic and improved versions of the bath composition and operating conditions are shown in Table 2.…”
Section: Thiourea Bathmentioning
confidence: 99%
See 1 more Smart Citation
“…Baths Containing No Additional Reducing Agent Recently, Krulik and Mandich [83] discovered that the Au(I) sulfite-thiosulfate system functions as an autocatalytic gold plating bath without adding any conventional reducing agent. Such a bath was found to plate 0.03-0.3 mm of gold in 15min at pH 6.5-9.0 and 55-75 C directly on electroless nickel deposited on copper-clad epoxy glass laminated printed circuit board.…”
Section: Baths Containing Both Sulfite and Thiosulfatementioning
confidence: 99%